Notodontidae (Lepidoptera) of Kemerovo Province (Southern Siberia, Russia) - Dmitry A. Efimov; Alexey V. Korshunov; Pavel S. Morozov; Roman V. Yakovlev (Acta Biologica Sibirica, 2024)
An overview of Notodontidae species composition of Kemerovo Province is given in the article. At present time, 28 species of 13 Notodontidae genera are registered. Two species (Cerura przewalskii (Alphéraky, 1882) and Notodonta dembowskii Oberthür, 1879) are recorded from Kemerovo Province for the first time.